SISTEM PENYELEKSI MAHASISWA BARU BERBASIS WEB MENGGUNAKAN METODE WEIGHTED PRODUCT - Arifin Tua Purba; Victor Marudut Mulia Siregar (Politeknik Bisnis Indonesia, 2020)
This research was conducted aiming to design a New Student Selection Decision Support System. To help the selection process for new student admissions at the Indonesian Business Polytechnic, a decision support system (SPK) was designed to help the data processing of prospective new students who register using the Weighted Product (WP) method. This Weighted Product method is done by using multiplication to link the attribute rating, where the rating of each attribute must be raised first with the weight of the attribute in question. The criteria used in this Decision Support System consist of: capacity, achievement, academic tests, age, and passing scores. From the sample of data examined, the ranking results were found to be the best value of prospective students with a value of 0.0841 and 0.0791.